2015
DOI: 10.1136/emermed-2015-204692
|View full text |Cite
|
Sign up to set email alerts
|

Serial sampling of copeptin levels improves diagnosis and risk stratification in patients presenting with chest pain: results from the CHOPIN trial

Abstract: Patients with chest pain with an initial negative troponin but positive copeptin are common and carry an intermediate risk of AMI. A second copeptin drawn 2 h after presentation may help risk stratify and potentially rule out AMI in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Because of the limited sensitivity of the electrocardiogram (ECG) and conventional cTn assays, the safe rule-out of AMI requires a second cTn sample and a second ECG recording 6-12 h after presentation if a conventional cTn assay is used. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] A shorter, 1 h or 3 h, protocol can be used with high sensitivity assays. 23,25,26 The delay in ruling out AMI can interfere with the detection of the underlying disease, increase patient anxiety, and is associated with substantial use of resources in the emergency department (ED), which contributes to ED crowding and its associated medical and economic harm.…”
Section: Need For Early Rule-out Of Amimentioning
confidence: 99%
“…Because of the limited sensitivity of the electrocardiogram (ECG) and conventional cTn assays, the safe rule-out of AMI requires a second cTn sample and a second ECG recording 6-12 h after presentation if a conventional cTn assay is used. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] A shorter, 1 h or 3 h, protocol can be used with high sensitivity assays. 23,25,26 The delay in ruling out AMI can interfere with the detection of the underlying disease, increase patient anxiety, and is associated with substantial use of resources in the emergency department (ED), which contributes to ED crowding and its associated medical and economic harm.…”
Section: Need For Early Rule-out Of Amimentioning
confidence: 99%
“…Despite a rise in normetanephrine across the assault exposure and evidence of a strong relationship between copeptin and osmolality, changes in cortisol, normetanephrine and osmolality did not reflect T cMax as well as copeptin and sCr. As described in the introduction, copeptin has been found to be of prognostic value in various conditions such as sepsis (Seligman et al 2008 ), septic and haemorrhagic shock (Morgenthaler et al 2007 ), in lower respiratory tract infections (Müller et al 2007 ), heart failure (Stoiser et al 2006 ) and myocardial infarction (Marston et al 2016 ). We report for the first time an initial association between increased copeptin and higher physiological strain under thermal stress.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy subjects performing a high altitude trek, plasma concentrations of copeptin and AVP associated closely and the correlation was strengthened ( r = 0.834, p < 0.001) at the highest and most stressful measurement point (Mellor et al 2015 ). In disease, copeptin has been found to be of prognostic value in diverse conditions such as sepsis (Seligman et al 2008 ), septic and haemorrhagic shock (Morgenthaler et al 2007 ), lower respiratory tract infections (Müller et al 2007 ), cardio- and cerebrovascular disease (Sun et al 2015 ; Stoiser et al 2006 ; Marston et al 2016 ; Greisenegger et al 2015 ) and for end stage renal failure, coronary heart disease and all-cause mortality in patients with type 1 diabetes (Velho et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The limit of quantification (LoQ) was 1.23 pmol/L, and the analytical measurable range (AMR) was 500 pmol/L. Initial studies used a copeptin cut-off level of 14 pmol/L; however, recent studies have suggested that a 10 pmol/L cut-off level might be more appropriate for ruling out early AMI [1415]. Accordingly, we used a second-generation copeptin assay and 10 pmol/L as the cut-off level.…”
Section: Methodsmentioning
confidence: 99%